2006
DOI: 10.1039/b607882f
|View full text |Cite
|
Sign up to set email alerts
|

The reaction products of the 193 nm photolysis of vinyl bromide and vinyl chloride studied by time-resolved Fourier transform infrared emission spectroscopy

Abstract: Time-resolved Fourier transform infrared (TRFTIR) emission spectroscopy has been used to study the 193 nm photolysis of vinyl bromide (C(2)H(3)Br) and vinyl chloride (C(2)H(3)Cl). Time-resolved IR emission was analysed to obtain nascent vibrational state populations of two primary photolysis products: HBr (v = 1-7) and HCl (v = 1-6). In both cases the nascent vibrational state populations monotonically decrease with increasing v and are in excellent agreement with previously published data. Time-resolved popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
3
14
0
1
Order By: Relevance
“…8,15 More recently these efforts have been supplemented with cavity ring down techniques, by Fahr et al 7 in the near-UV as well as Pibel et al 12 in the visible region, which now permit even more sensitive time-resolved chemical-kinetic studies of vinyl species. Recent broadband detection of vinyl radical by time-resolved FTIR emission studies has also been demonstrated by Letendre et al 11 and Carvalho et al, 20 though still at a spectral resolution unable to address issues of large-amplitude H atom migration.…”
Section: Introductionmentioning
confidence: 92%
“…8,15 More recently these efforts have been supplemented with cavity ring down techniques, by Fahr et al 7 in the near-UV as well as Pibel et al 12 in the visible region, which now permit even more sensitive time-resolved chemical-kinetic studies of vinyl species. Recent broadband detection of vinyl radical by time-resolved FTIR emission studies has also been demonstrated by Letendre et al 11 and Carvalho et al, 20 though still at a spectral resolution unable to address issues of large-amplitude H atom migration.…”
Section: Introductionmentioning
confidence: 92%
“…Several experimental studies have reported measurements of absorption bands to different electronic states of the VR in the last few decades. 11,[13][14][15][16][17][18][19][20] However, much of the experimental work has dealt with rovibrational spectroscopy of the double well and the tunneling dynamics of the VR in the ground X ˜2A 0 electronic state through the lowest-lying transition state. In this sense, infrared spectra [21][22][23] and tunneling splittings of the VR have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…e transitions of vibrationally excited hydrogen bromide HBr (1-3) have been attributed to the bands occurring between 2,400 cm -1 and 2,700 cm −1 [61,62,64]. Furthermore, a solid deposit has been seen clinging to the cell walls and windows.…”
Section: Ftir Spectroscopy Study Of the Soot Depositsmentioning
confidence: 97%